Upaya Meningkatkan Minat dan Hasil Belajar Siswa pada Pembelajaran IPA dengan Menggunakan Ice Breaking di Kelas IV SDN Puspasari – Jasinga - Suniyati Suniyati; Heri Dermawan; Irman Sumantri (Primer Edukasi Journal, 2022)
This study uses the classroom action research (CAR) method where researcher directly into the classroom to carry out teaching activities. This classroom action research consists of Pre-Cycle, Cycle I, and Cycle II. Research data in the form of student learning interests are obtained through the distribution of questionnaires while student learning outcomes data are obtained through tests at the end of each cycle. Based on the research data, it can be concluded that the use of ice breaking can increase student interest in learning science for class IV at SDN Puspasari-Jasinga. This can be seen from the increase in the average results of student learning interest questionnaires. The result of the average value of the student learning interest questionnaire in the pre-cycle were 70%, in the fisrt (fisrt) cycle it got an average of 75% and increased in the second (second) cycle to 83% with a very high description. Meanwhile, with KKM value of 70, it shows that in the precycle 9 students complete this 30% in the less level, in the fisrt cycle 25 students complete 50% are still in the Less level and in the second cycle 26 students complete this 87% in the Very Good level means improvement of 12 completed students. From the explanation above, it can be concluded that the use of ice breaking can increase the interest and learning outcomes of fourth-grade students.